Pola Asuh Akhlak bagi Anak dalam Keluarga Pernikahan Dini - Natatsa Syifaul Wardah; Erhamwilda; Sobar Al Ghazal (UNISBA Press, 2024)
Abstract. The first and foremost educators are our own parents, where they are responsible for the progress and development of their children, because a child's success really depends on the care, attention and education provided by their parents. Education is an important aspect in the formation of quality personal or human resources. Moral education in the family is very important because religion can provide guidance on the right path, leading to a path that is approved by Allah. This is in accordance with the opinion that